The impact of a training program built on learning technology on changing parents' attitudes toward accepting their autistic children in the center of Sulaymaniyah Governorate - Araz Hakem Radha; Renas Babakr Khdir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The reserach aims to identify: the effectiveness of a training program based on mobile learning technology in modifying parents' attitudes towards accepting their autistic children in the center of Sulaymaniyah Governorate. This was done by verifying the validity of the following hypothesis: There are no statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group members in modifying parents' attitudes towards accepting their autistic children before and after the application of the training program. And the training program does not achieve its effectiveness in modifying parents' attitudes towards accepting their autistic children with members of the experimental group. The research was limited to parents of autistic children in the center of Sulaymaniyah Governorate during the year (2020-2021). The researchers used an Experimental Design Quasi, and the research sample consisted of (16) parents of autistic children, where the researchers put them in one experimental group in order to apply the program to them. Then the researchers built a training program based on mobile learning technology (the Zoom educational program) especially, in addition to extracting the fave validity, the number of sessions was (9), and two sessions per week, and the duration of each session was (40 minutes). In order to measure the parents’ attitude towards accepting their autistic children, the researchers used the (Farran, 2003) scale, after extracting the face validity and reliability for the scale. The researchers used the Statistical Package for Social Sciences (SPSS) to analyze the research data. The results of the research concluded: There is a statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group members in the dimensions of the parents' attitude scale towards accepting their autistic children before and after the application of the training program expect for the fifth dimension (excess protection) of the scale. Thuse, the use of the training program is effective in modifying the attitude of parents towards accepting their autistic children, meaning that the participating parents have benefited from the training program, except for their attitude in the fifth dimension, which is (excess protection).